Analisis Epistemologi Pembelajaran Al-Qur’an di Madrasah Ibtidaiyyah Program Khusus Pondok Pesantren Imam Bukhari Surakarta - Mujiburrohman, Mujiburrohman; Tamyiz, Achmad (Lembaga Yasin AlSys, 2026)
The development of Al-Qur’an learning in Islamic primary education institutions requires a solid epistemological foundation so that the transmission of knowledge is not merely technical but also aligned with the aims of Islamic education. This study aimed to analyze the sources and methods of Al-Qur’an knowledge applied in the learning process at Madrasah Ibtidaiyyah Program Khusus (MI PK) Ponpes Imam Bukhari Surakarta from the perspective of the epistemology of the philosophy of Islamic education. A descriptive qualitative approach was employed, with data collected through in-depth interviews with three teachers, classroom observations, and curriculum documentation review. The findings show that Al-Qur’an learning at MI PK fundamentally positions revelation (Al-Qur’an and Sunnah) as the primary source of knowledge, with a dominance of the bayani (textual) method implemented through the talaqqi and tahfizh system as a form of commitment to the transmission of authoritative and authentic knowledge. The study concludes that the epistemology of Al-Qur’an learning at MI PK Ponpes Imam Bukhari is characterized by a tauhidi epistemology that prioritizes the authority of the sacred text and the teacher’s sanad, while reason and the senses function as auxiliary instruments in understanding and internalizing the teachings of the Al-Qur’an.